DISTRIBUSI KONTEN TAYANGAN TELEVISI SWASTA LOKAL DI KOTA JEMBER MELALUI MEDIA ONLINE - Romdhi Fatkhur Rozi (Faculty of Humanities, Jember University, 2015)
Technological development and change in the broadcasting regulation cause television stations in Indonesia to modify their broadcasting strategy. One of the alternatives is to distribute broadcast television content into the online path through user generated content sites such as Youtube. In addition to getting free broadcast path and reach a wider audience, ease of access also monetize broadcast channel in order to earn advertising revenue from every impression through the online. The government regulation of changing broadcast technique from digital to analog lines, still has not been fully successful. It becomes the easiest way out for local television stations of Jember whose capital is limited to switch from analog broadcasting method to cheap or even free digital broadcasting. With an online distribution, television stations can distribute contents and accessible to viewers through digital devices in a more flexible way, as long as connected to the internet. Television stations are also entitled to income from the number of viewers with contents uploaded to the site.Keywords: local private TV, user generated content, digital broadcasting, online media